Malaysiana gens to discover this weekend - Mohd Azmyl, Md Yusof * (The Malaysian Insight, 2023)
ONE way to view Malaysia through a different lens is to focus on Malaysiana—a term used to describe cultural objects and activities that embody elements considered Malaysian.